Mesenchymal Stem Cells for Regeneration of Cartilage Lesions: Focus on knee osteoarthritis - Kristjánsson, MS, Baldur; Mabey, BS, Thomas; Yuktanandana, MD, Pongsak; Parkpian, MD, Vinai; Honsawek, MD, Sittisak (Journal of Southeast Asian Orthopaedics, 2022)
With an increase in life expectancy which causes an ageing population, osteoarthritis, including cartilage loss and other cartilage lesions can become a major health problem. Cartilage has little self-renewal or regeneration capacity and those with cartilage lesions suffer from slow degeneration of the cartilage resulting in pain and loss of function. Conventional treatment for cartilage lesions often results in little or no pain relief leaving major surgery as the only viable option for improving the quality of life. Even so, available surgeries are not a permanent relief of the condition nor do they reverse the process of cartilage degeneration. Limited research funding, low public attention and a poor understanding of the mechanisms behind the conditions are several reasons that contribute to the lack of progress in developing treatments for cartilage degenerative conditions. In addition, cartilage degeneration is usually a slow process and early detection is often difficult due to the lack of biomarkers. In recent years, new methods have been suggested such as the use of autologous mesenchymal stem cells as a treatment of conditions like osteoarthritis. Clinical trials in both animal and human models have shown good results suggesting a simple, effective and lasting solution for cartilage lesions might be around the corner.